ETHNOBOTANICAL STUDY OF MEDICINAL FLORA IN BALODABAZAR-BHATAPARA DISTRICT OF CHHATTISGARH - SHOBHANA KOSHLE,; DEEPA BISWAS, (The Bioscan, 2026)
The present ethnobotanical study was to record and describe the local and tribal medicinal plant knowledge of local and tribal community of the Balodabazar-Bhatapara district, Chhattisgarh, India. The focus of the study was to name and document the medicinal flora, their use in treatment, parts of the plants used, mode of preparation and mode of administration.